Do Health Insurance Mandates Spillover to Education? Evidence from Michigan's Autism Insurance Mandate - Riley Acton; Scott Andrew Imberman; Michael F. Lovenheim (Center for Economic Studies and ifo Institute (CESifo), 2019)
Social programs and mandates are usually studied in isolation, but interaction effects could create spillovers to other public goods. We examine how health insurance coverage affects the education of students with Autism Spectrum Disorder (ASD) in the context of state-mandated private therapy coverage. Since Medicaid benefits under the mandate were far weaker than under private insurance, we proxy for Medicaid ineligibility and estimate effects via triple-differences. While we find little change in ASD identification, the mandate crowds-out special education supports for students with ASD by shifting students to less restrictive environments and reducing the use of ASD specialized teacher consultants. A lack of short-run impact on achievement supports our interpretation of the service reductions as crowd-out and indicates that the shift does not academically harm students with ASD.
Keywords: I18; I21; 330; special education; health insurance; insurance mandate